2022
DOI: 10.1109/ojim.2022.3196739
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Bladder Volume Measurement Based on Fringe Effect of Electrical Impedance Tomography Sensors

Abstract: Patients with bladder dysfunction are unable to perceive bladder volume and urinate spontaneously, and hence usually require catheterization. Personalized catheterization can effectively reduce the risk of urinary tract infections caused by catheterization. Electrical impedance tomography (EIT) can provide an effective tool for personalized catheterization by monitoring bladder volume. This study exploits the fringe effect of a 2D EIT sensor to derive the 3D volumetric information about bladder and improve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Thus, in this work, we propose novel BI features to study BV-related information, as shown in Table 2 . Given that urine conducts electricity, the impedance value across the bladder is expected to decrease with urine production [ 38 ]. We confirmed such a phenomenon in our previous study with 30 pediatric patients [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in this work, we propose novel BI features to study BV-related information, as shown in Table 2 . Given that urine conducts electricity, the impedance value across the bladder is expected to decrease with urine production [ 38 ]. We confirmed such a phenomenon in our previous study with 30 pediatric patients [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to static imaging with ultrasound, CT or nuclear magnetic resonance, EIT allows continuous (up to a dozen hours) diagnostics of urinary tract function. The great advantages of this method are its low invasiveness, long-term evaluation of urinary tract function and the relatively low price of performing the test [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%